Study on the weakening mechanism of anchorage interface under the action of water. (October 2019) - Yao, Qiangling; Tang, Chuanjin; Zhu, Liu; Li, Zhenyu; Niu, Zhijun; Li, Xuehua
Abstract: In this paper, pull-out tests of bolt are carried out to investigate the relation between water inflow and bolt-resin interface. Then, water intrusion tests and ring shear tests are sequentially conducted on rock-like specimens to investigate the effects of moisture content on the shear bond strength and failure mode of the rock–resin interface. The results suggest that the shear bond strength is markedly affected by water and failure concentrates on the interface between rock and resin after immersion in water. When comparing shear tests results from specimens with different immersion methods, it is evident that the resins have low hydroscopic behavior. It is also evident that rock weakening after water intrusion is the main cause of shear bond strength reduction of the rock–resin interface. During the failure process of dry specimens, there is evidence of a resin bearing stage, a breaking point and a residual stage that dissipates. Also, the applied load plunges after peak stress is achieved in specimens with increasing moisture content. Highlights: the failure of the anchors - anchoring agents - rock interfaces. the effect of water on anchors. the effect of water on rock.